Model Pembelajaran Integrasi PAI dengan Elemen Jati Diri (Hidup Bersih dan Sehat) di TK ABA 7 Karangjati Blora - Putri Nur Wahyu Romadhona (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Abstract: This study aims to analyze the PAI integration learning model with identity elements (clean and healthy living) in group B students. The research used a qualitative approach with a case study research type. The research location was in ABA 7 Karangjati Kindergarten, Blora Regency, with 33 student informants and two teachers. Data collection techniques through observation, interviews, and documentation. The data validity test used a credibility test where this study used triangulation. Data analysis techniques used data condensation, data presentation, and drawing conclusions. The results of the study showed that the application of PAI integration learning with identity elements (clean and healthy living) increased students' awareness of environmental cleanliness, both at school and at home. In addition, changing 90% of student behavior in terms of cleanliness, students have thrown garbage in its place, picked up scattered garbage, rearranged what has been used when playing, studying, and so on. They have a sense of responsibility for themselves and the surrounding space. In this activity, 20% of teachers or parents continue to remind their children to maintain cleanliness in order to live a clean and healthy life.